Idiopathic Sclerosing Encapsulating Peritonitis: Abdominal Cocoon in a 50 year old male (Journal of Surgical Sciences, 2019)
Idiopathic Sclerosing Encapsulating Peritonitis (or abdominal cocoon) is a rare cause of small bowel obstruction, especially in adult population. Diagnosis is usually incidental at laparotomy. We report one such rare case, outlining the fact that an intra-operative surprise diagnosis could have been facilitated by previous investigations.Journal of Surgical Sciences (2015) Vol. 19 (2) : 75-79